Arabic WordNet semantic relations enrichment through morpho-lexical patterns - Boudabous, M. M.; Kammoun, N. C.; Khedher, N.; Belguith, L. H.; Sadat, F. (2013 1st International Conference on Communications, Signal Processing and Their Applications, 2013)
Arabic WordNet (AWN) ontology is one of the most interesting lexical resources for Modern Standard Arabic. Although, its development is based on Princeton WordNet, it suffers from some weaknesses such as the absence of some words and some semantic relations between synsets. In this paper we propose a linguistic method based on morpho-lexical patterns to add semantic relations between synsets in order to improve the AWN performance. This method relies on two steps: morpho-lexical patterns definition and Semantic relations enrichment. We will take advantage of defined patterns to propose a hybrid method for building Arabic ontology based on Wikipedia.